3D-Printed Scaffolds Promote Angiogenesis by Recruiting Antigen-Specific T Cells. (October 2022) - Li, Cuidi; Ma, Zhenjiang; Li, Wentao; Jie, Tianyang; Zhong, Liping; Chen, Hongfang; Wang, Wenhao; Wang, Jinwu; Cui, Wenguo; Zhao, Yongxiang
Abstract: The immune response after implantation is a primary determinant of the tissue-repair effects of three-dimensional (3D)-printed scaffolds. Thus, scaffolds that can subtly regulate immune responses may display extraordinary functions. Inspired by the angiogenesis promotion effect of humoral immune response, we covalently combined mesoporous silica microrod (MSR)/polyethyleneimine (PEI)/ovalbumin (OVA) self-assembled vaccines with 3D-printed calcium phosphate cement (CPC) scaffolds for local antigen-specific immune response activation. With the response activated, antigen-specific CD4 + T helper 2 (Th2) cells can be recruited to promote early angiogenesis. The silicon (Si) ions from MSRs can accelerate osteogenesis, with an adequate blood supply being provided. At room temperature, scaffolds with uniformly interconnected macropores were printed using a self-setting CPC-based printing paste, which promoted the uniform dispersion and structural preservation of functional polysaccharides oxidized hyaluronic acid (OHA) inside. Sustained release of OVA was achieved with MSR/PEI covalently attached to scaffolds rich in aldehyde groups as the vaccine carrier. The vaccine-loaded scaffolds effectively recruited and activated dendritic cells (DCs) for antigen presentation and promoted the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) in vitro . When embedded subcutaneously in vivo, the vaccine-loaded scaffolds increased the proportion of Th2 cells in the spleen and locally recruited antigen-specific T cells to promote angiogenesis in and around the scaffold. Furthermore, the result in a rat skull defect-repair model indicated that the antigen-specific vaccine-loaded scaffolds promoted the regeneration of vascularized bone. This method may provide a novel concept for patient-specific implant design for angiogenesis promotion.